Unmet needs of patients with COPD in Germany: a retrospective, cross-sectional study - Herth, Felix; Vogelmeier, Claus F.; Trudzinski, Franziska; Watz, Henrik; Skowasch, Dirk; Beeh, Kai-Michael; Compton, Chris; Mohan, Tharishini; Richter, Hartmut; Claussen, Jing; Bartel, Sabine (ERJ Open Research, 2025)
Background Earlier diagnosis and treatment of COPD, particularly preventing exacerbations, are key to slowing disease progression and reducing mortality. This study focused on the identification of patients in Germany with unstable COPD due to suboptimal treatments. - Methods The IQVIA™ LRx database, capturing 80% of Statutory Health Insurance prescriptions was used to identify patients with COPD using a machine-learning model. Patients with unstable COPD were identified through high prescriptions of oral corticosteroid (OCS) and/or rescue inhalers between April 2022 and March 2023. - Results The machine-learning model identified around 2.6 million treated patients with COPD, with 77% precision. The mean age was 71 years, 48% were female and 86% were aged ⩾60 years. About 14% patients (n=363k) exhibited unstable COPD due to high OCS prescriptions, while 10% patients (n=256k) had high rescue inhaler prescriptions. Among those with high OCS and high rescue inhaler prescriptions, respectively, 43% and 38% were on dual therapy, 17% and 21% were on single inhaler triple therapy, 14% and 16% were on multiple inhaler triple therapy, 11% and 9% were on monotherapy and 15% and 17% had no maintenance therapy. - Conclusions A substantial number of unstable COPD patients were either on suboptimal maintenance therapy (monotherapy or inhaled corticosteroid-based dual therapy) or not receiving any maintenance therapy. The study highlights a substantial need in Germany for improved maintenance therapy, which could reduce disease burden, improve disease stability and reduce reliance on OCS and rescue therapies, thereby minimising side effects.